Efecto de tres métodos de siembra de kudzú pueraria montana como cobertura viva en el cultivo de banano musa spp - Aguilar Cruz, Manuel Benigno (2006)
During the season of april to june, in the property “The Palmas” del sieges Tillales, canton The Guabo, the kudzú establishment was investigated Pueraria like covering of the floor in a banana tree plantation with the purpose of establishing the kindness of this technology, new in the region. The outlined objectives were: to determine the best method in sowing of the kudzú in a banana plantation; to evaluate the best distance in siembra of the kudzú like alive covering. Three sowing systems were studied; direct with seed, transplant of plants of six weeks, and estolones sowing; these associated to three densities of sowing 1.0, 1.5 and 2.o m between places and 1.5 among streets, giving origin to nine treatments. The treatments got ready in the banana tree plantation in a design in blocks with four repetitions, totalling 36 experimental units. The analyzed variables were: germination, nutrition of the floor, plant height, number of guides, longitude of guides, covering of the floor. The variance analyses in all the analyzed variables threw high significance for treatments and in the significance tests with the averages of treatments, they evidenced that in the systems of transplante sowing they went superior with relationship to the direct sowing, alone in the time required to reach covering indexes that skirt 85% to the 90 days. Of the sowing densities the discharge (1.0x 1.5) in the direct sowing it was superior with the best covering average.; for the systems of transplant sowing and estolones sowing, the density 1.5 x1.5 gave better results. In plant height, covering and longitude of guides. The covering of the floor with kudzú until the 90 days in that it was evaluated the changes in the fertility of the floor showed with a light increment in the fertility in the concerning thing to nitrogen, copper, calcium and magnesium.